Syntactic priming and children’s production and representation of the passive - Messenger, Katherine (The University of Edinburgh, 2009)
This thesis investigates children’s mental representation of syntactic structure and how their acquisition and production of syntax is affected by lexical and semantic factors, focusing on three- and four-year-old children. It focuses on a construction that has been a frequent subject of language acquisition research: the passive. It is often claimed that English-speaking children acquire the passive relatively late in language development (e.g. Horgan, 1978): previous studies have typically found unreliable comprehension and infrequent production of passives by children younger than five (e.g. Fraser et al., 1963). However, there is some evidence from studies providing an appropriate pragmatic context for passives (e.g. Crain et al., 1987) and studies which increase children’s exposure to passives (e.g. Whitehurst et al., 1974) to suggest that children can produce this structure at a younger age. Converging evidence comes from studies of syntactic priming, or the tendency to repeat syntactic structure (e.g. Bencini & Valian, 2008). Syntactic priming effects are potentially informative about the nature of syntactic representation, as they are assumed to reflect the repeated use of the same syntactic representation across successive utterances. With respect to language acquisition, syntactic priming effects can be informative about the extent to which children have acquired an abstract representation of a structure. Specifically, if children have a syntactic representation of the passive, then it should be possible to prime their production of passives, such that they should be more likely to produce passives after hearing passives than after hearing actives. Furthermore, by examining the conditions under which such priming occurs, it is possible to draw inferences about the nature of their passive representation. This thesis presents seven experiments, six using a syntactic priming paradigm, to examine children’s knowledge of passives. Experiment 1 establishes a syntactic priming effect for actives and passives in three- and four-year-old children, and shows that priming occurs for both structures within an experimental session, using a withinparticipants design. Experiments 2, 3 and 4 examine whether young children’s acquisition of the passive is semantically constrained. Experiments 2 and 3 show that children can be primed to produce passive responses by actional and non-actional passive primes. Experiment 4, a picture-sentence matching task, replicates the results of other studies, however, showing that children find subject-experiencer non-actional verb passives more difficult to understand than actional verb passives; this mis-match between the results from the different tasks suggests that some effects of verb-type may be task-related. Experiments 5 and 6 examine whether the observed priming effect could be a lexically-driven effect that is dependent on the repetition of function words (the preposition by or the passive auxiliary). They show that this explanation can be ruled out: children are more likely to produce passives following both passive primes that do not express the agent using a by-phrase and passive primes involving a different auxiliary verb. Experiment 7 examines the later development of passive structures by testing passive production in six- and nine-year-old children. It finds evidence that at six, they still have difficulties with the construction, however by nine, children have an adult-like representation of the passive. I conclude that by four, children have begun to develop a syntactic representation for the passive which is already common to a range of different possible forms(short, full, get and be), and which is not restricted to particular semantic classes of verb. However, these results also suggest that children do not fully master the passive construction before six: young children make morphological errors and errors mapping thematic roles to syntactic positions, even following passive primes. Hence children may acquire the purely syntactic aspects of the passive, leading to a syntactic priming effect, before they acquire other aspects of this structure, hence the children’s occasional errors producing passives.
Keywords: linguistics; language acquisition; psycholinguistics; syntactic priming; passives